2009
DOI: 10.1016/j.acvd.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Poor blood pressure control in general practice: In search of explanations

Abstract: The disappointing therapeutic results observed in the management of arterial hypertension do not arise only from poor application of guidelines by general practitioners. Reluctance to rely on blood pressure measurements, a perception that guidelines are revised frequently and are not always clear, and consideration of the general practitioner's activity in the patient's specific context are the main factors involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
8
1
2
Order By: Relevance
“…BP values in excess of national guidelines are common, 19, 20 particularly after stroke. 7, 2123 After adjustment for age, sex and other confounders that might influence a patient's BP, the probability of being controlled remained significantly lower for patients with history of diabetes and/or hypertension. These data suggest that increased efforts to improve hypertension management at discharge and follow-up may be beneficial to certain subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…BP values in excess of national guidelines are common, 19, 20 particularly after stroke. 7, 2123 After adjustment for age, sex and other confounders that might influence a patient's BP, the probability of being controlled remained significantly lower for patients with history of diabetes and/or hypertension. These data suggest that increased efforts to improve hypertension management at discharge and follow-up may be beneficial to certain subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic care, GPs are confronted with the problem that they have to keep the patient compliant over a long period of time, and that any drug treatment has to match up to other health goals and is influenced by psychosocial problems [16]. Chapman and co-authors found a sharp decline in drug-adherence to lipid and blood pressure lowering drugs to only 36% within one year, with the greatest drop occurring in the first three months [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the general population [6,7] have reported that between 50% and 76% of treated hypertensive patients had uncontrolled hypertension, that is, ≥ 140/90 mmHg. For those followed by GPs, the last published rate was 58%, showing a gap between recommendations and practice [8]. Furthermore, the more risk factors that hypertensive patients receiving primary prevention treatment have, the worse these risk factors are controlled [5,9,10].…”
Section: Introductionmentioning
confidence: 99%